SKILLS OF SCHOOL ADMINISTRATORS IN THE 21ST CENTURY THAT AFFECT THE EFFECTIVENESS OF EDUCATIONAL INSTITUTIONS IN THE NAKHON RATCHASIMA SECONDARY EDUCATIONAL SERVICE AREA OFFICE - Jantakul, Chanyut; Siripunyanan, Tanasak; Poomkong, Somsak (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2025)
This research pointed to study 1) the skills of school administrators in the 21st century in the Nakhon Ratchasima Secondary Educational Service Area Office, 2) the effectiveness of educational institutions in the Nakhon Ratchasima Secondary Educational Service Area Office, 3) the relationship between the skills of school administrators in the 21st century and the effectiveness of educational institutions in the Nakhon Ratchasima Secondary Education Service Area Office, and 4) the skills of school administrators in the 21st century that can anticipate the effectiveness of educational institutions in the Nakhon Ratchasima Secondary Education Service Area Office. This research assigned the experimental group as 314 educational personnel under the Nakhon Ratchasima Secondary Education Service Area Office, consisting of 50 administrators and 264 teachers, by stratified random sampling. The researcher collected data using a 5-level rating scale questionnaire. The data were analyzed by using percentage, mean, standard deviation, Pearson’s product moment correlation coefficient, and stepwise multiple regression analysis. The research results showed that 1) The skills of school administrators in the 21st century, in general, were at a high level. 2) The effectiveness of educational institutions, in general, was at a high level. 3) The skills of school administrators in the 21st century and the effectiveness of educational institutions in general, there is a clear consistency in the same direction (𝑟𝑥𝑦 =0.765) with statistical significance at the .01 level. 4) There are 4 of 5 skills of school administrators in the 21st century, can predict the effectiveness of educational institutions with statistical significance. The multiple regression analysis equation can be written in the form of raw scores as follows: Y´ = 2.345 + 0.420(X5) + 0.295(X2) + 0.185(X3) + 0.150(X1) And the multiple regression analysis equation can be written in the form of standard scores as follows: Z´ = 0.455(ZX5) + 0.315(ZX2) + 0.198(ZX3) + 0.172(ZX1)